Johan Johansen: Fremtidsstemmen i Grundtvig - Høirup, Henning (Grundtvig-Studier, 1960)
<span lang="EN-US" style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Johan Johansen: The Voice of Future in Grundtvig